Montovaná konstrukce ze železobetonu - Šimon, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Diplomová práce se zabývá návrhem nosných prvků montované skeletové konstrukce. Předmětem návrhu je vnitřní příčný, respektive podélný rámy haly, skládající se ze střešního železobetonového vazníku, sloupů, průvlaků a stropních nosníků. Veškeré zatížení působící na nosnou konstukce je přenášeno pomocí železobetonových kalichových patek. Ostatní části objektu nejsou v této práci řešeny. Obsah diplomové práce se skládá z výkresů sestavy dílců skeletu a na vypracování statického výpočtu dle platných mezních stavů. Výstupem každého statického výpočtu je výkres tvaru a výztuže.

The master thesis is about a design of supporting structure of prefabricated skeleton hall. The major part of a design are an internal trasverse and longitudinal frames, which contents roof reinforce concrete truss, columns, beam and ceiling joists. All the load acting to the bearing structure is transferred to the prefabricate footing made of reinforce concrete. Other parts of the bulding are not solved in this thesis. The content of the thesis consists of an assembly drawing of parts of the skeleton and the static calculation according to the actual international standards. The output of each static calculation is drawing of a shape of part and its reinforcement.
Prefabricated concrete structure
Keywords: Nosná konstrukce; montovaný skelet; sloup; vazník; průvlak; konzolová deska; kalichová patka; výztuž; železobeton; zatížení; kombinace zatížení; vnitřní síly; výkres výztuže; výkres tvaru; Supporting structure; mounted skeleton; column; truss; girder; cantilever plate; prefabricate footing; reinforcement; reinforce concrete; loads; combination of loading cases; internal forces; drawing of a reinforcement; drawing of a shape